The effect of milk and rapeseed protein on growth factors in 7–8 year-old healthy children – A randomized controlled trial. (October 2021) - Grenov, Benedikte; Larnkjær, Anni; Ritz, Christian; Michaelsen, Kim F.; Damsgaard, Camilla T.; Mølgaard, Christian
Abstract: Objective: Milk protein may stimulate linear growth through insulin-like growth factor-1 (IGF-1). However, the effect of plant proteins on growth factors is largely unknown. This study assesses the effect of combinations of milk and rapeseed protein versus milk protein alone on growth factors in children. Design: An exploratory 3-armed randomized, double-blind, controlled trial was conducted in 129 healthy 7–8 year-old Danish children. Children received 35 g milk and rapeseed protein (ratio 54:46 or 30:70) or 35 g milk protein per day for 4 weeks. The primary outcome was difference in IGF-1 changes between intervention groups after 4 weeks. Secondary outcomes included changes in IGF-1 after 1 week and changes in insulin-like growth factor binding protein-3 (IGFBP-3), IGF-1/IGFBP-3, insulin, height, weight and body composition after 1 and 4 weeks. Results were analysed by multiple linear mixed-effect models. Results: There were no differences in changes of plasma IGF-1, insulin-like growth factor binding protein-3 (IGFBP-3), IGF-1/IGFBP-3 ratio or insulin between groups after 1 or 4 weeks based on 89 complete cases ( P  > 0.10). IGF-1 increased by 13.7 (95% CI 9.7;17.7) ng/mL and 18.0 (14.0;22.0) ng/mL from baseline to week 1 and 4, respectively, a 16% increase during the intervention. Similarly, insulin increased by 31% (14; 50) and 33% (16; 53) from baseline to week 1 and 4. Fat-free mass index (FFMI) increments were higher with milk alone than rapeseed blends ( P  < 0.05), coinciding with a trend towards a lower height increment. Body mass index increased within all groups (P < 0.05), mainly due to an increase in FFMI ( P  < 0.01). Conclusion: There were no differences in changes of growth factors between the combinations of milk and rapeseed protein and milk protein alone in healthy, well-nourished children with a habitual intake of milk. Within groups, growth factors increased considerably. Future studies are needed to investigate how intakes of plant and animal proteins affect childhood growth. Highlights: Effects of milk and plant protein on growth factors was assessed in children. Milk+rapeseed or milk protein alone equivalent to 1 L milk/d for 4 weeks was given. There were no differences in changes of IGF-1 or insulin between groups. Within groups, IGF-1 and insulin increased considerably. Studies are needed to investigate how plant and animal proteins affect growth.